Pat Manson: a multifaceted career devoted to supporting research in the fields of information and education - Collier, Mel; McLean, Neil (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
Two of Pat Manson’s long-standing colleagues give a summary of her wide-ranging career from her early days in library technology development, through the heady period of European funding for library innovation and latterly into broader issues of communication, learning and internet policies.